2001
DOI: 10.1063/1.1410885
|View full text |Cite
|
Sign up to set email alerts
|

Magnetotransport properties of a single grain boundary in a bulk La–Ca–Mn–O material

Abstract: Besides the ''intrinsic'' colossal magnetoresistance effect observed in single crystals, the polycrystalline manganate compounds also exhibit an ''extrinsic'' magnetoresistance related to the presence of grain boundaries. We report electrical transport and magnetic measurements carried out on a bigrain sample extracted from a floating zone method-grown rod of calcium doped lanthanum manganate. Electrical resistance was measured both within a grain and across the grain boundary, between 20 and 300 K and from 0 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
32
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 29 publications
7
32
0
Order By: Relevance
“…2 and 3) and a far less pronounced one at T pin ≈ 190 K. Additionally, ρ(T ) exhibits two shallow minima, one is situated at T Above T c , the sample is a PM non-metal with an activated temperature dependence of resistivity, following ρ(T ) ∝ exp(E a /T ). The activation energy E a is found to be equal to 0.09 eV in agreement with that (about 0.1 eV) reported by other authors for single crystal and ceramic samples of La 1−x Ca x MnO 3 (x ≈ 0.33) [17,24,25,30]. It is known [1,2,3] that the conductivity of Camanganites increases enormously at the transition to the FM state.…”
Section: Resistive and Magnetoresistive Propertiessupporting
confidence: 89%
See 3 more Smart Citations
“…2 and 3) and a far less pronounced one at T pin ≈ 190 K. Additionally, ρ(T ) exhibits two shallow minima, one is situated at T Above T c , the sample is a PM non-metal with an activated temperature dependence of resistivity, following ρ(T ) ∝ exp(E a /T ). The activation energy E a is found to be equal to 0.09 eV in agreement with that (about 0.1 eV) reported by other authors for single crystal and ceramic samples of La 1−x Ca x MnO 3 (x ≈ 0.33) [17,24,25,30]. It is known [1,2,3] that the conductivity of Camanganites increases enormously at the transition to the FM state.…”
Section: Resistive and Magnetoresistive Propertiessupporting
confidence: 89%
“…The value of ρ(T p )/ρ(0) is about 200 for the sample studied. This is a high value, comparable with that of single crystals and epitaxial films of the best quality [2,24,25,30,31,32]. For ceramic samples, prepared by the solid-state reaction method, the ratio ρ(T p )/ρ(0) is usually far less (see Refs.…”
Section: Resistive and Magnetoresistive Propertiesmentioning
confidence: 79%
See 2 more Smart Citations
“…Such resistance changes observed near T C are viewed as canonical for DE systems [21] and are intrinsic, bulk properties. Some authors call this colossal magnetoresistance effect observed in good-quality single crystals the "intrinsic" as opposed to the "extrinsic" magnetoresistance exhibited by the polycrystalline manganites, which is related to the presence of grain boundaries (GB) [22]. The "extrinsic" magnetoresistive effects are known to be due to spin-dependent scattering or tunnelling processes at the grain boundaries, inhomogeneities, microcracks and macroscopic defects.…”
Section: +mentioning
confidence: 99%